Reconstruction of the Tontemboan-Indonesian Dictionary: Makela'i and Matana'i - Mandolang, Nova Olvie; Lotulung, Donald Ringgo; Ranuntu, Garryn Christian (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Language is an arbitrary sound-symbolic system used by members of social groups to collaborate, communicate, and identify themselves. The primary function of language is as a means of communication between human beings. (Chaer, 2014). The research entitled “Reconstruction of the Indonesian Wall Dictionary: Makala’i and Matana’i” aims to document the Wall language through dictionaries as a language defense effort. The method used in this research is the qualitative-descriptive method. Data in the form of linguistic data in the Tontwoan language is collected both through the existing Tontwall dictionary and from informants in the field. Next, the data is classified and then analyzed using the opinions of Bogdan and Taylor on qualitative research. Based on the research carried out, the following results were obtained: (1) there is an addition of consonant sounds to a specific word in the Matana’I dialect variation Tontan; (2) there is a minimum pair of certain words in the Tontana’i dialect, so there are differences in vocal sounds and consonants between the Makela’ie dialect and Matana'I dialekt variation; (3) there are defining differences between the dialect variations of Makela'i and the dialectic variation of Matana‘i.